The war anthropogenic impact on the conditions of the Desna river surface waters - Horoshkovа, L. A.; Menshov , O. I.; Korniichuk, Y. D.; Soloviova , A. O. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To provide a comprehensive environmental assessment of the condition of the surface waters of the Desna River in order to identify the main anthropogenic factors of impact, in particular the consequences of the war.Methods. System analysis, statistical data processing methods, retrospective dynamics analysis, and forecasting of future trends.Results. In order to assess the anthropogenic load, including that caused by the war, on the condition of the surface waters of the Desna River, an analysis was carried out using long-term data from the Water Monitoring Laboratory of the Desna Basin Water Resources Authority for the monitoring stations: Chernihiv, 200 km; Brovary, 20 km; and Kyiv, 3 km. The research was conducted for the following indicators: biochemical oxygen demand over 5 days (BOD₅) and dissolved oxygen, phosphate ions and ammonium ions, nitrite ions and nitrate ions, sulfate ions and chloride ions. Special attention was paid to the analysis of pollution of the surface waters of the Desna River originating from the territory of the Russian Federation. It was established that in 2024 the most significant pollution was recorded in Chernihiv. An increase in the BOD₅ level was observed, exceeding the MPC (maximum permissible concentration) levels, along with a sharp decrease in the dissolved oxygen level. This indicates the entry of organic pollutants into the waters of the Desna River, which led to intensified decomposition processes. After September 21, 2024, the situation improved, as evidenced by a decrease in the BOD₅ level and an increase in dissolved oxygen. It was proven that this resulted from the entry into the river of phosphate and ammonium ions, as well as nitrite ions. Similar studies were carried out for the Brovary (20 km) and Kyiv (3 km) stations. It was found that the inflow of pollutants from the territory of the Russian Federation into the Desna River after August 26, 2024, did not affect the BOD₅ values and dissolved oxygen levels at these sites.Conclusions. The study identified the main environmental problems of the Desna River, in particular organic and mineral pollution, disturbance of the hydrological regime, and a decrease in oxygen levels. It was established that in 2024 the Desna River near Chernihiv (Chernihiv station, 200 km) experienced the greatest anthropogenic impact. Deterioration of water quality indicators was recorded for all analyzed parameters. The situation was better at the other two stations. Pollution of the Desna River with nitrite ions was observed only at the Chernihiv (200 km) station and was not significant at the Brovary (20 km) or Kyiv (3 km) stations. Since the BOD₅ and dissolved oxygen indicators normalized at the end of September, there is reason to believe that self-purification of the surface waters in the river occurred.